Words that wound, bodies that shield: Corporeal responses to Westboro Baptist Church's hate speech. Issue 1 (2nd January 2016) - Murray, Billie
Abstract: In the following essay, I argue that the U.S. Supreme Court decision in Snyder v. Phelps, together with the symbolic and spatial contexts surrounding funeral picketing, enables and constrains particular modes of community response to hate speech. Exploring community responses to Westboro Baptist Church's hate speech reveals a mode of resistance based in corporeal presence, as counter-demonstrators' bodies are used to shield mourners from messages of hate. The corporeal nature of these responses reasserts the boundaries between the public and private, and the sacred and profane, in ways that judicial responses do not.